Age-Related changes in the morphological features of medial column of the proximal humerus in the Chinese population - Chang, Zuhao; Zhu, Zhengguo; Zhang, Wei; Chen, Hua; Liu, Yujie; Tang, Peifu (Frontiers in Surgery, 2023)
Background: Age-related changes in the medial column (MC) of the proximal humerus have a major impact on fracture management; however, the changes in the morphological features remain unclear. This study aimed to investigate the age-related changes in the morphological features of MC and present the morphological grading. Methods: One hundred computed tomography (CT) images of the proximal humerus of 100 individuals (19–95 years) were retrospectively obtained. The individuals were categorized into five age groups to quantify the differences among different ages; the youngest group (18–44 years) served as the baseline group. Parameters of the morphological features were measured on CT images with multiplanar reconstruction based on an explicit definition of MC, including length, thickness, width, oblique thickness (DSM), humeral head diameter (DHM), and ratio (RSM) of DSM to DHM. The morphological grading of MC was presented based on the value of RSM deviating different standard deviations (SD) from the mean value in the baseline group. Results: Significant negative correlations were observed between age and the morphological parameters of MC (r ranged from −0.875 to −0.926; all P < 0.05), excluding DHM (r = 0.081, P = 0.422). Significant differences in the values of morphological feature parameters were detected among the five age groups (all P < 0.001). The highest mean values of morphological feature parameters were observed in the youngest group (18–44 years), which decreased gradually with increasing age until the lowest mean values were observed in the oldest group (≥90 years) (all P < 0.05). The morphological features of MC were categorized into three grades based on the value of RSM deviating 1.5 SD or 3 SD from the mean value in the baseline group. Conclusion: Our study shows that the parameter values of morphological features of MC decreased with increasing age. The morphological features of MC could be categorized into three grades. Our findings may provide a more comprehensive insight into age-related changes in the morphological features of MC that facilitate risk stratification and optimize the management of proximal humeral fractures.